2010
DOI: 10.1016/j.compscitech.2010.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Monotonic and cyclic short beam shear response of 3D woven composites

Abstract: a b s t r a c tMonotonic, multi-step and cyclic short beam shear tests were conducted on 2D and 3D woven composites. The test results were used to determine the effect of z-yarns on the inter-laminar shear strength as well as the multi-loading behavior. The presence of z-yarns was found to affect not only the inter-laminar shear strength of the composite but also the behavior of the composite beyond the elastic limit. Microscopic examination of the damaged specimens revealed large delamination cracks in 2D wov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The effect of z-binding yarns on the flexural and interlaminar shear strength of 3D woven composites has been studied by Cox et al 1994;Wang 2006;Walter et al 2010;Behera and Dash 2015;Dai et al 2015a;Umer et al 2016;Labanieh et al 2017). For ORT and 3D braided architecture, Wang et al (Wang 2006) reported both the flexural "3-point bending" and ILSS responses.…”
Section: Flexural and Interlaminar Shear Strength Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of z-binding yarns on the flexural and interlaminar shear strength of 3D woven composites has been studied by Cox et al 1994;Wang 2006;Walter et al 2010;Behera and Dash 2015;Dai et al 2015a;Umer et al 2016;Labanieh et al 2017). For ORT and 3D braided architecture, Wang et al (Wang 2006) reported both the flexural "3-point bending" and ILSS responses.…”
Section: Flexural and Interlaminar Shear Strength Testingmentioning
confidence: 99%
“…AI (Cox et al , 1996Pochiraju 1999;Mouritz and Cox 2010;Gerlach et al 2012;Mubeen 2014;Behera and Dash 2015;Yu et al 2015a;Dai et al 2015a;) Pochiraju 1999;Mouritz and Cox 2010;Behera and Dash 2015;Dai et al 2015a) (Pochiraju 1999;Buchanan et al 2012;Saleh et al2016c) Mouritz and Cox 2010;Yang et al 2014;Behera and Dash 2015;Dai et al 2015a;Umer et al 2016) Mouritz and Cox 2010;Walter et al 2010) LTL (Cox et al , 1996Callus et al 1999;Pochiraju 1999;Stig and Hallström 2009;Mubeen 2014;Warren et al 2015a;Yu et al 2015a;) Mouritz et al 1999b Lomov et al 2009;Dai et al 2015aDai et al , 2015bWarren et al 2015a;Castaneda et al 2016;Saleh et al 2016a, c;Labanieh et al 2017) Lomov et al 2009Lomov et al , 2011a…”
mentioning
confidence: 99%
“…The other issue is that the failure mode is superimposed by both flexure and shear. Several researchers such as Ishikawa et al [18], Stig et al [20], Abali et al [32], Li et al [33], Walter et al [34] and Phar et al [35] have investigated the problems associated with using short beam test. They have all proposed different modifications to existing setup for improving the results.…”
Section: Tensile Testingmentioning
confidence: 99%
“…The principle of 3DOWF is to bind straight warp and weft yarns together by using Z-yarns which run through the whole thickness of fabric. Since the existence of Z-yarns in the 3-D structures, the composite has advantages of delamination resistance and damage tolerance in comparison to 2D woven composite due to Z yarn [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%